Improving accuracy in percutaneous lung puncture using thoracic respiratory synchronization and laser angle guidance - Yang, Qingjie; Li, Qingtian; Lv, Shenghua; Lan, Linhui; Wang, Mingyang; Han, Kaibao (Frontiers in Medical Technology, 2025)
ObjectiveTo explore the feasibility of enhancing the accuracy of percutaneous lung puncture through matching the respiratory activity of the thorax and performing puncture under the guidance of a laser angle guider.MethodsA retrospective case-control study was adopted. Collected data of patients with pulmonary nodules undergoing puncture. They were categorized into the conventional puncture group (Con group), the laser guidance group (Laser group), and the thoracic respiratory activity matching group (Ram group) based on whether the puncture was guided by the laser angle guider and the application of the thorax respiratory activity matching technique.Results277 patients were included: 96 in the Con group, 93 in the Laser group, and 88 in the Ram group. There were no statistically significant differences in the puncture purpose, age, gender, BMI, maximum diameter of pulmonary nodules, location of pulmonary nodules, and distance from the skin at the puncture point among the three groups (P > 0.05). Nevertheless, key outcomes showed the Ram group had better results than the Laser group, which were better than the Con group: the rate of reaching the predetermined position on the first puncture (67.05% vs. 37.63% vs. 23.96%), number of CT scans (3.66 ± 1.06 vs. 4.09 ± 1.05 vs. 4.50 ± 1.08 times), and procedure time (23.05 ± 13.89 vs. 28.83 ± 13.78 vs. 35.14 ± 14.20 min) (all P < 0.05). Complication rates were sequentially lower (7.95% vs. 16.13% vs. 26.04%; P = 0.146).ConclusionPuncture by matching the thoracic respiratory activity and under the guidance of a laser angle guider can effectively improve the accuracy of percutaneous lung puncture, reduce complications. Furthermore, the procedure is straightforward, warranting further evaluation in larger, prospective studies.Clinical trial registrationChinese Clinical Trial Registry (ChiCTR), identifier (ChiCTR2300069384).